1987
DOI: 10.1111/j.1469-8749.1987.tb02103.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback Techniques and Behaviour Modification in the Conservative Remediation of Drooling by Children With Cerebral Palsy

Abstract: SUMMARY In an attempt to decrease the rates of drooling of 12 children with cerebral palsy, the authors investigated the effectiveness of EMG auditory feedback training of the orbicularis oris, of making the act of swallowing a conscious one, and of providing an auditory signal to cue swallowing by means of an Accularm interval timer. After biofeedback training there was a significant decrease in drooling rates and a small increase in swallowing rates. After the Accularm was used the children maintained the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 14 publications
0
27
0
3
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Most articles (76%) were published between 1977 and 1987. After 1994, no study on behaviour treatment for drooling appeared.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Most articles (76%) were published between 1977 and 1987. After 1994, no study on behaviour treatment for drooling appeared.…”
Section: Resultsmentioning
confidence: 99%
“…In four studies [14][15][16]22 no interobserver reliability was reported. In the other studies, interobserver reliability appeared to be consistently high: above 70%.…”
Section: Dependent Variables and Reliabilitymentioning
confidence: 99%
See 3 more Smart Citations